2018
DOI: 10.1007/s12369-017-0421-z
|View full text |Cite
|
Sign up to set email alerts
|

Assistive Robotic Technology to Combat Social Isolation in Acute Hospital Settings

Abstract: Social isolation in hospitals is a well established risk factor for complications such as cognitive decline and depression. Assistive robotic technology has the potential to combat this problem, but first it is critical to investigate how hospital patients react to this technology. In order to address this question, we introduced a remotely operated NAO humanoid robot which conversed, made jokes, played music, danced and exercised with patients in a London hospital. In total, 49 patients aged between 18-100 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Enablers, such as enjoyment and personalisation, were mainly related to the use of robots at an individual level. The element of enjoyment in the HRI was also elsewhere found to be crucial among hospital patients,49 opening the doors for considering social humanoid robots as an intervention to combat social isolation in hospital settings.…”
Section: Discussionmentioning
confidence: 94%
“…Enablers, such as enjoyment and personalisation, were mainly related to the use of robots at an individual level. The element of enjoyment in the HRI was also elsewhere found to be crucial among hospital patients,49 opening the doors for considering social humanoid robots as an intervention to combat social isolation in hospital settings.…”
Section: Discussionmentioning
confidence: 94%
“…This finding is consistent with the results from previous studies [2,75,76] that robots have been widely used to treat children with ASD by promoting their social behaviors and improving their communication skills. Our results also revealed that CIs were adopted to manage chronic diseases, such as stroke [46], cancer [47], and dementia [77]. These health issues usually require long-term treatment and intensive care.…”
Section: Discussionmentioning
confidence: 75%
“…In addition to developing conversational opportunities, direct social robots could act as entertainers, e.g. showing pictures or playing music for residents, as has been done with NAO humanoid robots ( Sarabia et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%